Speaker dependent malay connected digit speech recognition using continuous density hidden Markov model - Zuraimi Yahya; Sheikh Hussain Shaikh Salleh, 1958-; Ting, Chee Ming; Ahmad Kamarul Ariff Ibrahim@Ahmad; Tan, Tian Swee; International Conference on Man-Machine system (2006 : Kedah) (Skudai : Universiti Teknologi Malaysia, 2006)
16